2008
DOI: 10.1007/s10751-008-9734-5
|View full text |Cite
|
Sign up to set email alerts
|

A structural and Mössbauer study of Y3Fe5O12 nanoparticles prepared with high energy ball milling and subsequent sintering

Abstract: The influence of ball milling and subsequent sintering of a 3:5 molar mixture of Y 2 O 3 and α-Fe 2 O 3 on the formation of nanocrystalline Y 3 Fe 5 O 12 (YIG) particles is studied. Pre-milling the mixture for 100 h lowers the onset temperature at which the material forms to 900 • C which is 200 • C lower than that reported when a similar mixture of reactants was premilled for shorter times. A single-phased nanocrystalline Y 3 Fe 5 O 12 phase develops as a sole product when the pre-milled mixture is heated at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 17 publications
(18 reference statements)
1
8
0
Order By: Relevance
“…1(a)), we can see the measured spectra (hollow black circles) with their respective fits (thick color solid curves): one sextet (green 1 curve) accounts for Fe 3+ ions at sites with octahedral symmetry 16(a 1 ), whereas the other one (blue curve) corresponds to Fe 3+ at tetrahedral coordinated sites 24(d). Thus, these two sextets are an indicative of the YIG phase [19,32,33] and they are present in all composites (YIG 0.75 CTO 0.25 , YIG 0.50 CTO 0.50 and YIG 0.25 CTO 0.75 , Fig. 1(b)-(d), respectively).…”
Section: Resultsmentioning
confidence: 77%
“…1(a)), we can see the measured spectra (hollow black circles) with their respective fits (thick color solid curves): one sextet (green 1 curve) accounts for Fe 3+ ions at sites with octahedral symmetry 16(a 1 ), whereas the other one (blue curve) corresponds to Fe 3+ at tetrahedral coordinated sites 24(d). Thus, these two sextets are an indicative of the YIG phase [19,32,33] and they are present in all composites (YIG 0.75 CTO 0.25 , YIG 0.50 CTO 0.50 and YIG 0.25 CTO 0.75 , Fig. 1(b)-(d), respectively).…”
Section: Resultsmentioning
confidence: 77%
“…7,[225][226][227][228][229][230][231][232][233][234][235][236][237][238][239][240][241] In this sense MCS represents a comparatively new technological approach to preparation of ultra-disperse nanosized oxides without any thermal treatment (one-step mechanochemical route) 225,230 or with some partial heating at a lower temperature and for a shorter time. 233 Distinctive features of the complex oxides prepared by the MCS method are the new compounds 235,242 or the new energetic, 225 structural, 227 dispersion 227 or electronic states of already known compositions. 243 The mechanochemical processing provides an opportunity to fabricate novel nanomaterials with anomalous properties different from those of bulk samples prepared by conventional (ceramic, sintering, co-precipitation, hydrothermal) processing.…”
Section: Oxidesmentioning
confidence: 99%
“…[225][226][227][228][229][230][231][232] In the latter case, the mechanical treatment involving velocities of the rotating body up to 100, 250, and 390 rpm is considered to be low-energy, medium-energy and high-energy processing, respectively. 245 The ratios of the weight of a ball in a ball mill to the weight of the sample being ground (BPR) that have been applied were as follows: 50 : 1, 225 30 : 1, 241d 20 : 1, 226,227,237,242,243 15 : 1, 233 13 : 1 230 and 10 : 1. 231 The absence of normative regulations with respect to the conditions of treatment does not allow results to be obtained on the same basis that could be compared regarding the mechanochemical activation of powders having one and the same chemical nature.…”
Section: Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Paesano et al [15] reported the successful mechanosynthesis of YIG from a mixture of Y 2 O 3 and Fe 2 O 3 followed by an annealing at 1000˚C. Widatallah et al [16] presented a detailed study of the influence of the milling process on the formation of single phase YIG by mechanochemical synthesis, using similar experimental conditions to those reported by Paesano [15]. Also, M. Niyaifar et al [2] used high energy milling to mechanically activate the powder mixture of BiO, Y 2 O 3 , and Fe 2 O 3 and achieve doped Bi-YIG complete synthesis by subsequent annealing at high temperature.…”
Section: Introductionmentioning
confidence: 99%